(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Juvenile delinquency has been identified as a major issue in India and around the world. There is no denying that today’s delinquent boy, if not adequately cared for, will become a criminal tomorrow. Children’s delinquency should be regulated until it becomes a major threat to society. According to psychology, any child between the ages of 15 and 18 who commits a crime, regardless of whether he is apprehended or not, is considered a juvenile delinquent. In this sense, a juvenile delinquent is somebody who takes another’s property forcibly or damages it, engages in anti-social behaviour, threatens another’s life, or obstructs others’ activities. From a psychological perspective, a child who throws a stone at a vehicle and runs away, one who sets fire without purpose, and one who puts another’s life in danger just for the fun of it are all examples of juvenile delinquency.